Universalism Vs. Cultural Relativism dan Implementasinya dalam Hak Kebebasan Beragama Di Indonesia - Belardo Prasetya Mega Jaya; Muhammad Rusli Arafat (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2017)
The result of this research showed that universalism put human right (HAM) as universal values as formulated in International Bills of Human Rights. Human rights have been naturally owned by an individual. This is the universal nature of those rights where human rights are a natural rights theory and apply to anyone and everywhere. These rights cannot revoked by anyone, and also cannot be transferred from human to other human or regulated by the state. The State is obliged to fulfill those rights. In contrast to cultural relativism, which rejects the view of universal rights. Human rights must be placed in a particular cultural context in each country. Culture is the only source of legitimate rights or moral rules.